2021
DOI: 10.1002/ange.202104476
|View full text |Cite
|
Sign up to set email alerts
|

Multienzyme One‐Pot Cascades Incorporating Methyltransferases for the Strategic Diversification of Tetrahydroisoquinoline Alkaloids

Abstract: The tetrahydroisoquinoline (THIQ) ring system is present in a large variety of structurally diverse natural products exhibiting a wide range of biological activities. Routes to mimic the biosynthetic pathways to such alkaloids, by building cascade reactions in vitro, represents a successful strategy and can offer better stereoselectivities than traditional synthetic methods. S‐Adenosylmethionine (SAM)‐dependent methyltransferases are crucial in the biosynthesis and diversification of THIQs; however, their appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…Hailes and co-workers recently extended this work, adding different O-and N-methyltransferases (MTs) to obtain several THIQ methylated derivatives (Scheme 5q). [172] The methyltransferases chosen were SAM dependent. However, SAM is a cost-intensive cofactor, and it limits the applicability of MT-catalyzed reactions on large scale.…”
Section: Tetrahydroisoquinoline (Thiq) Derivativesmentioning
confidence: 99%
“…Hailes and co-workers recently extended this work, adding different O-and N-methyltransferases (MTs) to obtain several THIQ methylated derivatives (Scheme 5q). [172] The methyltransferases chosen were SAM dependent. However, SAM is a cost-intensive cofactor, and it limits the applicability of MT-catalyzed reactions on large scale.…”
Section: Tetrahydroisoquinoline (Thiq) Derivativesmentioning
confidence: 99%
“…[30,140] In general, enzyme kits of other classes such as hydrolases (e. g., lipases and esterases) and ketoreductases have existed for decades [1,2] and are commercially available from many different companies. [3,4] Furthermore, enzyme kits of yet less well investigated classes such as methyltransferases [141][142][143] for the selective alkylation (e. g., methylation and carboxymethylation) of natural products of lead drugs should be highly valuable for synthetic (pharmaceutical) chemists, [144][145][146] especially since the discovery of the 'magic methyl effect'. [147,148] Scheme 4.…”
Section: Future Outlook For Enzyme Kitsmentioning
confidence: 99%
“…In previous studies it was found that the COMT from Myxococcus xanthus (MxSafC) was also able to perform a double methylation of tetrahydroisoqunolines while the related enzyme from Rattus norvegicus (RnCOMT) transferred only one methyl group regioselectively. [32] Different classification systems have been suggested to distinguish between similar enzymes. Regarding plant hydroxyl O-MTs, Joshi et al introduced a classification system dividing O-MTs into class I and II, according to their amino acid sequence, size and dependence on metal ions.…”
Section: Introductionmentioning
confidence: 99%
“…This includes catechol O‐ MTs (COMTs) known for the O‐ methylation of dopamine. In previous studies it was found that the COMT from Myxococcus xanthus (Mx SafC) was also able to perform a double methylation of tetrahydroisoqunolines while the related enzyme from Rattus norvegicus ( Rn COMT) transferred only one methyl group regioselectively [32] . Different classification systems have been suggested to distinguish between similar enzymes.…”
Section: Introductionmentioning
confidence: 99%